Tingkat Stres dengan Penyalahgunaan Alkohol pada Remaja Laki-laki - Dewa Made Ruspawan (Jurnal Gema Keperawatan, 2013)
The purpose of this research is to find the relation between stress level with boys alcohol abuse in Banjar Belatung, Senganan, Keridan, Desa Senganan, Bali. This research is an analityc observationalresearch which used cros sectional approachment to find the relation between stress level with boys alcohol abuse. The data is collecting by stress and alcohol abuse questionnaire with sample consists of 149 boys. The result of the research showed that most of boys is on middle stress as much as 27 boys (34,6%) and 70 boys (89,7%) is on alcohol abuse. According to the result of Rank Spearman correlation test sig (1 tailed) value is .000 which means Ho is denied and there is a relationship  between stress level and boys alcohol abuse. With Coefficient Contingency value 0,546 means that the relation between the two variable is strong.